Differential Genetic and Environmental Influences on Reactive and Proactive Aggression in Children - Baker, Laura A. (2008)
While significant heritability for childhood aggression has been claimed, it is not known whether there are differential genetic and environmental contributions to proactive and reactive forms of aggression in children. This study quantifies genetic and environmental contributions to these two forms of aggression in an ethnically diverse urban sample of 9–10 year old twins (N=1219), and compares results across different informants (child self-report, mother, and teacher ratings) using the Reactive–Proactive Aggression Questionnaire (RPQ). Confirmatory factor analysis of RPQ items indicated a significant and strong fit for a two-factor proactive–reactive model which was significantly superior to a one-factor model and which replicated across gender as well as the three informant sources. Males scored significantly higher than females on both self-report reactive and proactive aggression, findings that replicated on mother and teacher versions of the RPQ. Asian–Americans scored lower than most ethnic groups on reactive aggression yet were equivalent to Caucasians on proactive aggression. African–Americans scored higher than other ethnic groups on all measures of aggression except caregiver reports. Heritable influences were found for both forms of aggression across informants, but while boys' self-reports revealed genetic influences on proactive (50%) and reactive (38%) aggression, shared and non-shared environmental influences almost entirely accounted for girls' self-report reactive and proactive aggression. Although genetic correlations between reactive and proactive aggression were significant across informants, there was evidence that the genetic correlation was less than unity in boys self reported aggression, indicating that genetic factors differ for proactive and reactive aggression. These findings provide the first evidence for varying genetic and environmental etiologies for reactive and proactive aggression across gender, and provide additional support for distinction between these two forms of aggression.